Pilot test for bioremediation of soils contaminated by hydrocarbons. Phase ll (2009)
The study of the biodegradation of highly polluting and toxic hydrocarbon compounds is of interest for the decontamination of environments affected by oil spills. Although this process occurs naturally, it is too slow, which is why the use of bioremediation techniques is necessary to facilitate microbial action on contaminants. At the experimental level, this process is carried out in stages or tests, be they laboratory, pilot, field or implementation. Previous to this study, a stage was worked at the laboratory level, where the removal of hydrocarbon in an induced contaminated soil was observed, isolating bacteria capable of degradation, which showed that the process is feasible. The present study corresponds to the stage at the pilot level, the objective of which was to quantify the rate of hydrocarbon removal in soil samples contaminated with castile oil from ten terrariums, to which total bacteria and Pseudomonas aeruginosa bacteria were inoculated.